Telaah Konseptual Komunikasi Transendental Dalam Perspektif Komunikasi Islam - Abdur Razzaq (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2022)
Abstract: This article discusses the interrelationship of transcendental communication as part of Islamic communication. Transcendental communication is part of communication practices that are never separated from the daily life of a Muslim in carrying out the commands of Allah SWT. By using a descriptive qualitative method, this paper presents a narrated study through the collection of data from relevant references. The results of the study show that transcendental communication in Islam can be carried out through various media known as rituals of worship, both obligatory worship and sunnah worship. Worship which describes the concept of transcendental communication in the practice of communication carried out by Muslims with Allah SWT. Transcendental communication in prayer can be likened to God as the receiver (communicant), while the actor acts as the sender of the message (communicator), the source is the perpetrators or the events experienced, the medium (channel) is prayer, (effect) is the peace of mind that we will get or other symbols and signs that God sends to humans. The focus of the discussion is on matters relating to the application of transcendental communication which is associated with worship behavior which is a means of communication with Allah SWT.